Gender identification of mouse embryos using the polymerase chain reaction (PCR) technique - Abdullah, Ramli; Mohamed Said, M.S.; Nor Ashikin, M.N.K.; Froemming, G.A.R.; Mohamed, Z.; Nor Shahida, A.R. (2006)
A multiplex nested PCR technique was used to identify gender from single blastomeres biopsied from 8-cell mouse embryos. The primers amplified sequences of the Sry and Zfy genes on the Y-chromosome, and a polymorphic X chromosome microsatellite locus (DXNds-3). Amplification of male DNA gave three bands, of sizes 217 bp (Zfy), 147 bp (Sry) and 111 bp (Nds). In contrast, amplification of female DNA gave a single band of 111 bp (Nds). Test on blood DNA showed a 98.0% PCR amplification efficiency whereas single blastomeres produced 93.0% PCR amplification efficiency. In conclusion, mouse embryos were successfully sexed within 6 hours by using single blastomeres obtained from 8-cell embryos.